2021
DOI: 10.3389/fpls.2021.736613
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Application of Straw-Derived Fulvic Acid on Yield and Quality of Tomato Plants Grown in a Greenhouse

Abstract: Fulvic acids are organic compounds widely distributed in soils, and the application of fulvic acids is thought to increase crop yield and quality. However, the effects vary among various sources and doses of fulvic acids and environmental and growth conditions of crops. Here, we investigated the effects of bioresource-derived (corn straw) fulvic acids on plant production and quality of tomato plants and soil chemical properties in soil cultures while experiments on seed germination and hydroponics were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In the experiments of Karashchuk et al (2020) the germination energy of winter wheat seeds treated with Quadrastim with succinic acid increased by 3-8% from the control, field germination was higher by 4-7%. For pre-sowing treatment of tomato seeds, soaking in fulvic acid with a concentration of 80 mg/l is recommended, where germination increased by 13%, and root lengthby 32% compared to the control (Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments of Karashchuk et al (2020) the germination energy of winter wheat seeds treated with Quadrastim with succinic acid increased by 3-8% from the control, field germination was higher by 4-7%. For pre-sowing treatment of tomato seeds, soaking in fulvic acid with a concentration of 80 mg/l is recommended, where germination increased by 13%, and root lengthby 32% compared to the control (Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the positive impact of HA and FA on the growth and development of various crops, such as tomato, cucumber, maize, rice, wheat, and others (Atiyeh et al, 2002; Zhang et al, 2021; Hartwigsen & Evans, 2000; Liang et al, 2023). Our study reveals that the addition of FA can significantly promote maize growth under low nitrogen stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pirlak and Kose (2009), did not find significant differences in fruit Ph when applying rhizobacteria of the genus Pseudomonas and Bacillus in strawberry cultivation. In another study carried out by Zhang et al (2021) when applying fulvic acids in the tomato crop via foliar spray, the pH of the fruit increased by 1%. These increases in fruit pH found in this research are possibly explained by what Rodríguez et al (2004) reported, indicating that, the pH increases as the fruit reaches maturity, thus providing the characteristic flavor of the fruit, according to the species.…”
Section: Quality Variables In Strawberry Cultivationmentioning
confidence: 96%